Modelling for Control: Combination of Education Approaches. Issue 2 (2020) - Atanasijević-Kunc, Maja; Karer, Gorazd; Zdešar, Andrej
Abstract: At the University of Ljubljana, Faculty of Electrical Engineering we have introduced several years ago the Bologna study. At the postgraduate or master level, students can choose among eight different possible study fields, where one is Control systems and computer engineering. In the first semester of this study field, all students have to attend the course entitled Modelling methods. As students come from different faculties, their first-level education differs. As a consequence, some additional effort is needed each year to adjust the knowledge, which is very important for all the participants, while new lessons have to be presented in a suitable manner as well. This has to be realized taking into account the available hours for this course and the personal knowledge of all students. The problem was addressed through the combination of different approaches: through the modular organization of the lectures and laboratory exercises, through e-learning extensions, through the development of Matlab toolbox, and through the project-oriented work and exams, which enable additional research activity with the possibility of students' competition participation and/or presentation and publication of research results. Such an organization seems to have significant motivation potential.